Bone scintigraphy and positron emission tomography in the early diagnosis of MRONJ - Pergolini Daniele; Mohsen Mohamed; Tenore Gianluca; Palaia Gaspare; Magnifico Lorenzo; Del Vecchio Alessandro; Romeo Umberto (Open Medicine)
The aim of this study is to evaluate the bone scintigraphy (BS) and positron emission tomography (PET) in the early diagnosis of medication-related osteonecrosis of the jaws (MRONJ) and their possible use in the identification of patients at risk for MRONJ.